ANALYTICAL SCREENING OF CERTAIN MEHAGHNA AND PRAMEHAGHNA PLANTS OF CHARAK SAMHITA WITH SPECIAL REFERENCE TO ANTI-DIABETIC STUDIES - G.C., Nanda (International Journal of Ayurveda and Pharma Research, 2016)
Diabetes mellitus has become a challenge for human civilisation due to want of dependable and safer medicines. Though modern science has stepped up to maximum with the help of technological advancement but still the alternative approach stands as option, Ayurveda has described the complete treatment package for the disease Prameha/Madhumeha as it is compared with the disease Prameha/ Madhumeha in Ayurveda. Different inter disciplinary etiopathogenesis are met with suitable scientific evaluations for its treatment. The herbal drugs are playing vital role in drug research in world scenario today. Several classical books are famous for their description of medicinal plants with various pharmacological values. Ayurveda has the answer for complete management of Diabetes mellitus as evident from the available treatises. Several herbs/plants are now been identified having antidiabetic effects today by the researchers but Charak Samhita an age old treatise of Ayurveda bears a lot of description about the potent plants/drugs for various diseases out of which certain Pramehaghna/ Madhumehaghna plants are of concern. In 6th chapter of Charak Chikitsa several plants/plant materials have been identified working in Prameha/Madhumeha. Few plants selected from this chapter were taken to compare its efficacy in Diabetes at par with the available experimental/clinical studies. A search was made in the paper only to find out specific few plants described as Pramehaghna /Mehaghna in Charak Samhita to verify with experimental/clinical anti-diabetic study so for done and it was found that the plants so described in Charak samhita are having the anti-diabetic activities it would be praiseworthy to mention here that the result will find out a better way of solution in treating Diabetes Mellitus with further extensive trails.